Ageing and multiple sclerosis - Graves, Jennifer S; Krysko, Kristen M; Hua, Le H; Absinta, Martina; Franklin, Robin J M; Segal, Benjamin M (Lancet neurology, 2023)
The factor that is most relevant and strongly associated with the clinical course of multiple sclerosis is chronological age. Very young patients exclusively have relapsing remitting disease, whereas those with later onset disease face a more rapid development of permanent disability. For people with progressive multiple sclerosis, the poor response to current disease modifying therapies might be related to ageing in the immune system and CNS. Ageing is also associated with increased risks of side-effects caused by some multiple sclerosis therapies. Both somatic and reproductive ageing processes might contribute to development of progressive multiple sclerosis. Understanding the role of ageing in immune and neural cell function in patients with multiple sclerosis might be key to halting non-relapse-related progression. The growing literature on potential therapies that target senescent cells and ageing processes might provide effective strategies for remyelination and neuroprotection.